In Pursuit of Alignment and Affiliation: The Practice of Anchoring Shared Knowledge in Japanese Conversation. Issue 2 (7th February 2021) - Kaneyasu, Michiko
ABSTRACT: Conversational interactants rely on each other to cooperate with ongoing actions and activities both structurally (alignment) and affectively (affiliation). They monitor one another's cooperative behaviors to detect any (potential) problems in alignment and affiliation. The present study describes one interactional strategy Japanese speakers use to deal with detected problems in three nonmain sequences (i.e., side, preexpansion, and postexpansion sequences). In the practice I call anchoring shared knowledge, the action (or activity) initiator uses the utterance-final desho to request ratification of shared knowledge from the recipient. Positioning of this request relative to the main action makes the desho -speaker's action interpretable to the recipient as seeking alignment to and affiliation with the main action. The study demonstrates (a) the interactants' constant attention to alignment and affiliation, (b) their orientation to the relevance of local practices to the main action or activity, and (c) the complex interrelationships between epistemics, actions, and social relations.